PENAMBAHAN TEPUNG DAGING IKAN PATIN (Pangasius hypopthalmus) TERHADAP TINGKAT KESUKAAN STICK BAWANG - Rani Pratiwi (Jurnal Perikanan Unram, 2024)
Stick is a type of snack that is long and flat with a savory and crunchy taste, made from wheat flour, eggs, salt, margarine, and water. Stick is generally made from main ingredients such as wheat flour, tapioca, and other starch sources with high carbohydrate content but low in other nutrients, thus necessitating the addition or fortification of other energy source nutrients like fat, protein, vitamins, and minerals. The addition of patin fish meat flour to onion stick products will affect the protein content; furthermore, the addition of flour to the product will impact the preference level of the onion stick. The aim of this research is to determine the optimal level of patin fish meat flour addition in the production of onion sticks to create the most preferred product. The method used is experimental, consisting of four treatments of patin fish meat flour addition: 0%, 12.5%, 15%, and 17.5%. The parameters observed in this study include a preference test (hedonic), analyzed using non-parametric statistics with the Friedman test, followed by a multiple comparison test and a Bayes test for decision making, and a proximate test to determine moisture content, ash content, fat content, protein content, and carbohydrate content. The results of the hedonic test indicated that onion sticks with 15% patin fish meat flour addition were the most preferred by the panelists, with preference scores for color at 8.3; aroma at 8; taste at 8; and texture at 7.9. The proximate content for the 15% treatment was 4.35% moisture; 2.17% ash; 36.56% fat; 9.31% protein; and 52.39% carbohydrate.